I am trying to solve a double summation problem. But the result I get is different than the one already published in a research paper. Can anyone please find where I am making mistake. I tried the following:
While the correct result is:
Follow Math Help Forum on Facebook and Google+
For this problem I noticed that the indices of the inner summations were from h to w_i - 1 but it looks like the expression accounts for an extra term since you have w_i - h instead of w_h - 1 - h.
Let me clear it.
sum (k=h to w_i - 1) = sum (k=1 to w_i-1) - sum (k=1 to h-1)= (w_i - 1) - (h-1) = w_i - h;
I hope this is what you were talking about.
Please someone help me, this is the second time I am posting this.
Thanks for that clarification. I will take a look at this later on.
View Tag Cloud